Effective synthesis of circRNA via a thermostable T7 RNA polymerase variant as the catalyst - He, Wei; Zhang, Xinya; Zou, Yangxiaoyu; Li, Ji; Chang, Le; He, Yu-Cai; Jin, Qiuheng; Ye, Jianren (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: CircularRNA (circRNAs) are endogenous noncoding RNAs (ncRNAs) with transcriptional lengths ranging from hundreds to thousands. circRNAs have attracted attention owing to their stable structure and ability to treat complicated diseases. Our objective was to create a one-step reaction for circRNA synthesis using wild-type T7 RNA polymerase as the catalyst. However, T7 RNA polymerase is thermally unstable, and we streamlined circRNA synthesis via consensus and folding free energy calculations for hotspot selection. Because of the thermal instability, the permuted introns and exons (PIE) method for circRNA synthesis is conducted via tandem catalysis with a transcription reaction at a low temperature and linear RNA precursor cyclization at a high temperature.Methods: To streamline the process, a multisite mutant T7 RNA polymerase (S430P, N433T, S633P, F849I, F880Y, and G788A) with significantly improved thermostability was constructed, and G788A was used.Results: The resulting mutant exhibited stable activity at 45 °C for over an hour, enabling the implementation of a one-pot transcription and cyclization reaction. The simplified circRNA production process demonstrated an efficiency comparable to that of the conventional two-step reaction, with a cyclization rate exceeding 95% and reduced production of immunostimulatory dsRNA byproducts.